PENGEMBANGAN MEDIA PEMBELAJARAN BARUNG SILUNG BERBASIS ANDROID - CHRISTIAN, STEVEN; PRAYITNO, ANTON; WINARTO, BAMBANG (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research aims to develop android-based learning media on Curved Side Spaces material, and evaluate the feasibility of the developed media. This Android-based learning media development was developed using 4 (four) software, including: (1) Canva; (2) PowerPoint; (3) iSpring Suite; and (4) Website 2 APK Builder. In this study, the development model refers to the ADDIE development model, with its stages, namely: (1) Analysis; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. The research instruments include validation sheets for experts and student response questionnaires. The results of expert validation show an average feasibility of 83% (quite valid), while the results of student responses get an average of 79.5% (good). Based on these findings, the learning media “Barung Silung” is considered feasible to use to support math learning. This research is limited to the media development stage. ABSTRAKPenelitiani inii bertujuani untuki mengembangkan mediai pembelajarani berbasisi androidi pada materi Bangun Ruang Sisi Lengkung, serta mengevaluasi kelayakan media yang dikembangkan. Pengembangani mediai pembelajarani berbasisi Androidi ini dikembangkan menggunakan 4 (empat) software, di antaranya: (1) Canva; (2) PowerPoint; (3) iSpring Suite; dan (4) Website 2 APK Builder. Dalam penelitian ini, model pengembangannya mengacu pada model pengembangan ADDIE, dengan tahapani-itahapannya iyaitu: (1) iAnalysis (analisis); (2) Designi (desain); (3) Developmenti (pengembagan), (4) Implementationi (implementasi), (5) Evaluation (evaluasi). Instrumen penelitian meliputi lembar validasi untuk ahli dan angket respon siswa. Hasil validasi ahli menunjukkan rata-rata kelayakan sebesar 83% (cukup valid), sementara hasil respon siswa mendapatkan rata-rata 79,5% (baik). Berdasarkan temuan ini, media pembelajaran